Green Zone in the Architecture and Theory of English Brutalism during the 1950s and 1970s - Solomonova, Irina S. (Actual Problems of Theory and History of Art, 2024)
In modernist, especially functionalist, theory, nature was given a rationally justified hygienic function, which obviated the need for artistic design of landscapes. However, after World War II the architectural community started to feel the inadequacy of the functionalist method and sought to humanize it. The CIAM discussion developed new principles, based on the idea of communication and community building, as well as blending of functions like in the traditional city. It was presented by a group of young architects who called themselves ‘Team X’. On this basis, the group’s leaders, British architects Alison and Peter Smithson, created the New Brutalism which rapidly gained popularity in England. This article aims to explore the landscape architecture of the green space in Brutalist urbanism and housing in its relation to the theory and practice of green spaces in international modernism, the theory of Brutalism itself, and the critique of modernism that emerged at the turn of the 1950s and 1960s. Although the texts and declarations of the Brutalists themselves contain much fewer direct reference to the general principles of green spaces than program texts of Functionalism, there is a clear evolution and increasing complexity of in its design. Gradually they acquire a character of their own and become understood as part of a coherent urban communication system. Thus, the practices of the New Brutalism allowed a progressive sophistication of the relationship between the architecture and urban green spaces, which is of great importance for the subsequent existence of landscape architecture.
Keywords: green urban spaces; Brutalism; history of urban planning; architecture of 20th century